Structure Stability, Flame Retardancy, and Antimicrobial Properties of Polyurethane Composite Nanofibers Containing Tannic Acid and Boron‐Doped Carbon Nanotubes. Issue 11 (15th November 2021) - Kim, Young Nam; Jo, Jun Young; Kim, Yebom; Ha, Yu‐Mi; Han, Haksoo; Lee, Doh C.; Kim, Jaewoo; Jung, Yong Chae
Abstract : Front Cover : The development of tannic‐acid‐based textile materials is a good candidate that enables both flame retardancy and antibacterial properties. In article number 2100455, Jaewoo Kim, Yong Chae Jung, and co‐workers show that when nanocarbon materials are used together, it is possible to not only realize complex functions but also increase physical properties, thereby expanding the potential range of application of the materials.